Risk Evaluation of Urban Integrated Pipe Corridor Operation and Maintenance Based on Improved AHP-CIM Model - Shuai Wang; Shaochuan Fu (Discrete Dynamics in Nature and Society)
In order to scientifically and objectively evaluate the risk in the operation and maintenance process of the urban integrated pipe corridor, and then prevent the occurrence of urban integrated pipe corridor operation and maintenance accidents, this paper combines AHP analysis and CIM model to propose a new model for the risk assessment of pipe corridors: AHP-CIM model, and uses the model to conduct a verification of the operation and maintenance risk evaluation of the Beijing Tongzhou Canal Core Area North Ring Tunnel Integrated Pipe Corridor. Using a combination of qualitative and quantitative methods, the risk factors in the operation and maintenance process of the integrated urban pipe corridor were first identified and their weights determined, and then the CIM model was used to calculate the probability distribution of the levels of risk factors at each level of the hierarchical model, and finally the risk assessment set of the risk probability distribution of this integrated pipe corridor was obtained. The results show that the overall O&M risk level of this integrated pipe corridor is high, and its probability is 69.47%.